Genetically Engineered Crops: Experiences and Prospects - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Genetically engineered (GE) crops were first introduced commercially in the 1990s. After two decades of production, some groups and individuals remain critical of the technology based on their concerns about possible adverse effects on human health, the environment, and ethical considerations. At the same time, others are concerned that the technology is not reaching its potential to improve human health and the environment because of stringent regulations and reduced public funding to develop products offering more benefits to society. While the debate about these and other questions related to the genetic engineering techniques of the first 20 years goes on, emerging genetic-engineering technologies are adding new complexities to the conversation.
Keywords: Biology and Life Sciences; Agriculture

Air Emissions from Animal Feeding Operations: Current Knowledge, Future Needs - National Research Council (The National Academies Press, 2003)
Air Emissions from Animal Feeding Operations: Current Knowledge, Future Needs discusses the need for the U.S. Environmental Protection Agency to implement a new method for estimating the amount of ammonia, nitrous oxide, methane, and other pollutants emitted from livestock and poultry farms, and for determining how these emissions are dispersed in the atmosphere. The committee calls for the EPA and the U.S. Department of Agriculture to establish a joint council to coordinate and oversee short - and long-term research to estimate emissions from animal feeding operations accurately and to develop mitigation strategies. Their recommendation was for the joint council to focus its efforts first on those pollutants that pose the greatest risk to the environment and public health.
Keywords: Environment and Environmental Studies; Agriculture

The Scientific Basis for Estimating Air Emissions from Animal Feeding Operations: Interim Report - National Research Council (The National Academies Press, 2002)
This is an interim report of the ad hoc Committee on Air Emissions from Animal Feeding Operations of the National Research Council's Committee on Animal Nutrition. A final report is expected to be issued by the end of 2002. The interim report is intended to provide the committee's findings to date on assessment of the scientific issues involved in estimating air emissions from individual animal feeding operations (swine, beef, dairy, and poultry) as related to current animal production systems and practices in the United States. The committee's final report will include an additional assessment within eight broad categories: industry size and structure, emission measurement methodology, mitigation technology and best management plans, short- and long-term research priorities, alternative approaches for estimating emissions, human health and environmental impacts, economic analyses, and other potential air emissions of concern.This interim report focuses on identifying the scientific criteria needed to ensure that estimates of air emission rates are accurate, the basis for these criteria in the scientific literature, and uncertainties associated with them. It also includes an assessment of the emission-estimating approaches in a recent U.S. Environmental Protection Agency (EPA) report Air Emissions from Animal Feeding Operations. Finally, it identifies economic criteria needed to assess emission mitigation techniques and best management practices.
Keywords: Agriculture; Environment and Environmental Studies

Psoroptic Cattle Scabies Research: An Evaluation - National Research Council (The National Academies Press, 1979)
Keywords: Agriculture

An Assessment of Native Seed Needs and the Capacity for Their Supply: Final Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Extreme weather and wildfires, intensified by climate change, are damaging the native plant communities of landscapes across the United States. Native plant communities are foundational to thriving ecosystems, delivering goods and services that regulate the environment and support life, provide food and shelter for a wide range of native animals, and embody a wealth of genetic information with many beneficial applications. Restoring impaired ecosystems requires a supply of diverse native plant seeds that are well suited to the climates, soils, and other living species of the system. This report examines the needs for native plant restoration and other activities, provides recommendations for improving the reliability, predictability, and performance of the native seed supply, and presents an ambitious agenda for action. An Assessment of Native Seed Needs and the Capacity for Their Supply considers the various challenges facing our natural landscapes and calls for a coordinated public-private effort to scale-up and secure a cost-effective national native seed supply.
Keywords: Agriculture

Saline Agriculture: Salt-Tolerant Plants for Developing Countries - National Research Council (The National Academies Press, 1990)
Keywords: Agriculture

Pesticide Resistance: Strategies and Tactics for Management - National Research Council (The National Academies Press, 1986)
Based on a symposium sponsored by the Board on Agriculture, this comprehensive book explores the problem of pesticide resistance; suggests new approaches to monitor, control, or prevent resistance; and identifies the changes in public policy necessary to protect crops and human health from the ravages of pests. The volume synthesizes the most recent information from a wide range of disciplines, including entomology, genetics, plant pathology, biochemistry, economics, and public policy. It also suggests research avenues that would indicate how to counter future problems. A glossary provides the reader with additional guidance.
Keywords: Agriculture

Animal Research in a Global Environment: Meeting the Challenges: Proceedings of the November 2008 International Workshop - National Research Council (The National Academies Press, 2011)
Animal research will play an essential role in efforts to meet increasing demands for global health care. Yet the animal research community faces the challenge of overcoming negative impressions that industry and academia engage in international collaborations in order to conduct work in parts of the world where animal welfare standards are less stringent. Thus, the importance of ensuring the international harmonization of the principles and standards of animal care and use cannot be overstated. A number of national and international groups are actively working toward this goal. The Institute for Laboratory Animal Research (ILAR), a program unit of the US National Research Council, is committed to promoting both the welfare of animals used in research and the quality of the resulting science. In 2008, to follow up on the 2003 event, ILAR convened a workshop which brought together 200 participants from 17 countries. Their mission was to identify and promote better understanding of important challenges in the conduct of animal research across country boundaries. These challenges include: the sourcing of animals; the quality of veterinary care; competent staff; the provision of a suitable environment (including nutritious food and potable water) for animals; and ongoing oversight of the animal program; among others. Animal Research in a Global Environment summarizes the proceedings of the 2008 workshop. The impact of this 2008 workshop has extended beyond the oral presentations conveyed in these proceedings. It has been a vital bridge for diverse colleagues and organizations around the world to advance initiatives designed to fill gaps in standards, professional qualifications, and coordination of animal use.
Keywords: Biology and Life Sciences; Agriculture

Animal Health at the Crossroads: Preventing, Detecting, and Diagnosing Animal Diseases - National Research Council (The National Academies Press, 2005)
The confirmed case of "mad cow" disease (BSE) in June 2005 illustrates the economic impact of disease outbreaks, as additional countries closed their markets to U.S. beef and beef products. Emerging diseases also threaten public health—11 out of 12 of the major global disease outbreaks over the last decade were from zoonotic agents (that spread from animals to humans).
Keywords: Agriculture; Biology and Life Sciences

Nonhuman Primates: Usage and Availability for Biomedical Programs - National Research Council (The National Academies Press, 1975)
Keywords: Agriculture

Quality-Protein Maize: Report of an Ad Hoc Panel of the Advisory Committee on Technology Innovation Board on Science and Technology for International Development National Research Council, in Cooperation With the Board on Agriculture National Research Co - National Research Council (The National Academies Press, 1988)
Keywords: Agriculture

Agricultural Development and Environmental Research: American and Czechoslovak Perspectives: Proceedings of a Bilateral Workshop (The National Academies Press, 1987)
Keywords: Agriculture

Insect-Pest Management and Control - National Research Council (The National Academies Press, 1969)
Keywords: Agriculture

Races of Maize in Brazil and Other Eastern South American Countries (The National Academies Press, 1958)
Keywords: Agriculture

Control of Plant-Parasitic Nematodes - National Research Council (The National Academies Press, 1968)
Keywords: Agriculture

Guidelines for the Investigation of Grain Dust Explosions: Report - National Research Council (The National Academies Press, 1983)
Keywords: Agriculture

Workshop on Biotechnology in Agriculture: Summary Report, Jakarta, Indonesia, March 13-14, 1986 - National Research Council (The National Academies Press, 1986)
Keywords: Agriculture

Wild and Free-Roaming Horses and Burros: Current Knowledge and Recommended Research. - National Research Council (The National Academies Press, 1980)
Keywords: Agriculture

World Food and Nutrition Study: Enhancement of Food Production for the United States : a Report of the Board on Agriculture and Renewable Resources, Commission on Natural Resources, National Research Council, Prepared for the NRC Study on World Food and - National Research Council (The National Academies Press, 1975)
Keywords: Agriculture

Beef for Tomorrow: Conference Proceedings - National Research Council (The National Academies Press, 1960)
Keywords: Agriculture